Leprosy: A neurological masquerador - Ananta A Kulkarni; Suhas V Abhyankar; Madhuri Kulkarni; Rohit R Singh; Manjot Marwah (Wolters Kluwer Medknow Publications, 2015)
A 20-year-old male farmer with injury to the left hand, associated with weakness of the hand muscles and numbness, underwent ulnar and median nerve repair. An ultrasonography after 3 months was performed due to persistent weakness and numbness after surgery, which showed mass in the median nerve for which the patient underwent excision of neuroma and sural nerve grafting. The patient again presented after 3 months with weakness and numbness, and a nerve conduction study showed non-functioning ulnar and median nerve. A re-exploration showed mass in the ulnar nerve, which on biopsy showed borderline tuberculoid leprosy. This case report reflects a case of pure neuritic leprosy that was missed due to trauma as it was in the early phase and could only be diagnosed at the 3 rd exploration of the hand.